2008
DOI: 10.1086/591044
|View full text |Cite
|
Sign up to set email alerts
|

SpitzerIRAC and MIPS Imaging of Clusters and Outflows in Nine High‐Mass Star Forming Regions

Abstract: We present Spitzer Space Telescope IRAC and MIPS observations toward a sample of nine high-mass star forming regions at a distance of around 2 kpc. Based on IRAC and MIPS 24 m photometric results and 2MASS JHK s data, we carry out a census of young stellar objects (YSOs) in a 5 0 ; 5 0 field toward each region. Toward seven out of the nine regions, we detect parsec-sized clusters with around 20 YSOs surrounded by a more extended and sparse distribution of young stars and protostars. For the other two regions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
2

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 95 publications
(181 reference statements)
8
138
2
Order By: Relevance
“…Qiu et al (2008) found five-band Spitzer/IRAC and 2MASS H and K s emission towards 4-n, as well as Spitzer/IRAC 3.6 μm, 4.5 μm, 5.8 μm, and 8.0 μm emission towards 1/2/3-n. Source 4-n is likely at an early stage of evolution, although it is probably the most evolved source in the northern (proto)cluster.…”
Section: Continuum Sourcesmentioning
confidence: 73%
See 2 more Smart Citations
“…Qiu et al (2008) found five-band Spitzer/IRAC and 2MASS H and K s emission towards 4-n, as well as Spitzer/IRAC 3.6 μm, 4.5 μm, 5.8 μm, and 8.0 μm emission towards 1/2/3-n. Source 4-n is likely at an early stage of evolution, although it is probably the most evolved source in the northern (proto)cluster.…”
Section: Continuum Sourcesmentioning
confidence: 73%
“…We confirmed their estimation, finding that the visual extinction for 13-s is A v ∼ 2700 (see Table 2). Source 13-s is in an early stage of evolution, according to its NIR excess and the presence of H 2 O and Class ii CH 3 OH masers (Beuther et al 2002d), although the detection of a VLA 3.6 cm source at its position (Sridharan et al 2002), suggests that there is a recently ignited protostar that has already formed an ultracompact or hypercompact Hii region, the detected radio emission being consistent with an ionizing B2 V star (Martín-Hernández et al 2008;Qiu et al 2008;Panagia 1973).…”
Section: Continuum Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…For comparison, we also show (in Fig. 4b) the NH 3 (1, 1) integrated intensity map from Zhang et al (2002) overlaid with the cluster of infrared sources reported in recent studies (Hunter et al 1995;Chen et al 2005;Qiu et al 2008) in order to have a complete view of the stellar content in AFGL 5142. The overall structure of the integrated N 2 H + (1-0) emission consists of two main cores, located to the west and to the east of the dust condensation (hereafter western and eastern cores), surrounded by a more extended structure with an X-shape morphology, roughly following the same morphology as the NH 3 emission.…”
Section: Molecular Line Emission: N 2 H +mentioning
confidence: 99%
“…Recently, Qiu et al (2008) carried out Spitzer Space Telescope IRAC and MIPS observations toward AFGL 5142. The authors identify 44 YSOs, 20 of them clustered around the central massive star and surrounded by a more extended and sparse distribution of young stars and protostars.…”
Section: Introductionmentioning
confidence: 99%